RACHID GHANNOUCHI AND THE RISE OF MUSLIM DEMOCRAT IN TUNISIA’S POLITICS - Amir, ahmad nabil; Abdul Rahman, Tasnim (State Islamic University of Datokarama Palu, 2024)
The paper highlights Rachid Ghannouchi’s political ideas in the context of the growth of political Islam in the Arab world by focusing on historical and political development that underlie the democratic process in Tunisia. It discusses political idealism he developed in Ennahda movement (The Renaissance Party) based on the principles of freedom and justice and its uncompromising opposition to the autocratic regime of Habib Bourguiba (1957-1987) and his successor Zine el-Abidine Ben Ali (1987-2011). The study is qualitative in nature in the form of documentary and content analysis. It used descriptive, analytical and historical approaches to analyse data derived from established archival sources. The study found that Ennahda which was founded by Ghannouchi in 1980 had broad influence in mainstream Islamic politics in Tunisia, that espouse to dismantle the autocratic rule and decolonise the corrupt practice and political suppression of past regime. The influence it developed had broadly impacted both Islamic and secular forces to converge and commit toward democratic rule, human rights and the principle of justice, freedom, and the rule of law